Agriterribacter soli sp. nov., isolated from herbicide-contaminated soil. Issue 6 (14th June 2022) - Song, Man; Mao, Zhen-Bo; Liu, Yuan; Wang, Guang-Li; Li, Feng; Zhang, Long
Abstract : A Gram-stain-negative, non-spore-forming and rod-shaped bacterium, designated strain NS-102 T, was isolated from herbicide-contaminated soil sampled in Nanjing, PR China, and its taxonomic status was investigated by a polyphasic approach. Cell growth of strain NS-102 T occurred at 16–42 °C (optimum, 30 °C), at pH 5.0–8.0 (optimum, pH 6.0) and in the presence of 0–3.5 % (w/v) NaCl (optimum, without addition of NaCl). The 16S rRNA gene sequence of strain NS-102 T shows high similarity to that of Agriterribacter humi YJ03 T (96.9 % similarity), followed by Terrimonas terrae T16R-129 T (93.8 %) and Terrimonas pekingensis QH T (93.6 %). Average nucleotide identity, average amino acid identity and digital DNA–DNA hybridization values between the draft genomes of strain NS-102 T and A. humi YJ03 T were 72.5, 69.4 and 18.6%, respectively. The only respiratory quinone was MK-7, and phosphatidylethanolamine and unidentified lipids were the major polar lipids. The major cellular fatty acids of strain NS-102 T contained high amounts of iso-C15 : 0 (24.6 %), iso-C17 : 0 3-OH (24.1 %), iso-C15 : 0 G (16.6 %) and summed feature 3 (C16 : 1  ω 6 c and/or C16 : 1  ω 7 c ) (15.6 %). The G+C content of the total DNA was determined to be 40.0 mol%. The morphological, physiological, chemotaxonomic and phylogenetic analyses clearly distinguished this strain from its closest phylogenetic neighbours. Thus, strain NS-102 T represents a novel species of the genus Agriterribacter, for which the name Agriterribacter soli sp. nov. is proposed. The type strain is NS-102 T (=CCTCC AB 2017249 T =KCTC 62322 T ).